Deciphering Pro-angiogenic Transcription Factor Profiles in Hypoxic Human Endothelial Cells by Combined Bioinformatics and in vitro Modeling - Schmidt, Arne; Fuchs, Maximilian; Stojanović, Stevan D.; Liang, Chunguang; Schmidt, Kevin; Jung, Mira; Xiao, Ke; Weusthoff, Jan; Just, Annette; Pfanne, Angelika; Distler, Jörg H. W.; Dandekar, Thomas; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Constant supply of oxygen is crucial for multicellular tissue homeostasis and energy metabolism in cardiac tissue. As a first response to acute hypoxia, endothelial cells (ECs) promote recruitment and adherence of immune cells to the dysbalanced endothelial cell barrier by releasing inflammatory mediators and growth factors, whereas chronic hypoxia leads to the activation of a transcription factor battery that potently induces expression of growth factors and cytokines including platelet-derived growth factor and vascular endothelial growth factor. We report a hypoxia-minded, targeted bioinformatics approach aiming to identify and validate transcription factors that regulate angiogenic signaling. Results: A comprehensive RNA-Seq dataset derived from human ECs subjected to normoxic or hypoxic conditions was selected to identify significantly regulated genes based on (i) fold change (normoxia vs hypoxia) and (ii) relative abundancy. Transcriptional regulation of this gene set was confirmed via qPCR in validation experiments where HUVECs were subjected to hypoxic conditions for 24 h. Screening the promoter and upstream regulatory elements of these genes identified two transcription factors, KLF5 and SP1, both with a potential binding site within these regions of selected target genes. In vitro, siRNA experiments confirmed SP1- and KLF5-mediated regulation of identified hypoxia-sensitive endothelial genes. Next to angiogenic signaling, we also validated the impact of transcription factors on inflammatory signaling, both key events in hypoxic sensing. Both transcription factors impacted on inflammatory signaling since endogenous repression led to increased NF-κB signaling. Additionally, SP1 silencing eventuated decreased angiogenic properties in terms of proliferation and tube formation. Conclusion: By detailed in silico analysis of promoter region and upstream regulatory elements for a list of hypoxia-sensitive genes, our bioinformatics approach identified putative binding sites for transcription factors of SP or KLF family in vitro. This strategy helped to identify transcription factors functionally involved in human angiogenic signaling and therefore serves as a base for identifying novel RNA-based drug entities in a therapeutic setting of vascularization.